Synthesis, growth inhibitory activity on human tumor cell lines and evaluation of the hepatotoxicity of di(hetero)arylethers and di(hetero)arylamines in the thieno[3,2-b]pyridine series. - Calhelha, Ricardo C. (2013)
Thienopyridine skeleton has been reported as having interesting biological activity, namely antitumor [1] and antiangiogenic [2] activities. Herein we describe the synthesis of di(hetero)arylethers 1a-f and di(hetero)arylamines 2a-f functionalizing the 7-position of the thieno[3,2-b]pyridine in good to high yields, using copper (C-O) or palladium (C-N) catalyzed couplings, like presented below. The growth inhibitory activity of the di(hetero)arylethers 1a-f and di(hetero)arylamines 2a-f was evaluated against five human tumor cell lines (breast- MCF-7, non-small cell lung- NCI-H460, colon- HCT15- hepatocellular- HepG2 and cervical- HeLa carcinomes), using the sulforhodamine B assay. Furthermore, the hepatotoxicity of compounds was studied using a porcine liver primary cell culture (PLP2). The most promising compounds were shown to be the methoxy derivatives 1e and 2e, presenting GI50 values comparable with ellipticine (control) without hepatotoxicity. For these compounds more studies are needed to find out their mechanisms of action.